The sheriff : America's defense of the new world order - Gray, Colin S. (University Press of Kentucky, 2009)
Since the end of the Cold War, and especially since September 11, 2001, few issues have been more hotly debated than the United States' role in the world. In this hard-nosed but sophisticated examination, Colin S. Gray argues that America is the indispensable guardian of the world order. Gray's constructive critique of recent trends in national security is comprehensive, rooting defense issues and prospective answers in both U.S. national security policy and in the emerging international security environment.